A TRI-SIKKHA BASED INSTRUCTIONAL SYSTEM TO ENHANCE ACHIEVEMENT LEARNING DEVELOPMENT OF SOCIAL TEACHING STUDIES FOR HIGH SCHOOL STUDENTS NAKORNSAWAN PROVINCE - (Siwankam), Phramaha Supalurk Supattajari; Siriwat, Chawal; (Booncham), Phra Widesbrommakun (Journal of MCU Nakhondhat, 2024)
This research article aims to: 1) Study the knowledge of developing a social studies teaching system based on the Threefold Training (Tri-Sikkha) principles, 2) Assess the current problems and needs of the social studies teaching system based on the Threefold Training principles, 3) Develop a social studies teaching system based on the Threefold Training principles, and 4) Evaluate and certify the development of the social studies teaching system based on the Threefold Training principles to enhance the academic achievement of high school students in Nakhon Sawan Province. This study used a Research and Development methodology. The sample group consisted of 100 students, and 10 administrators and experts (monks/individuals) were interviewed using a purposive sampling method. The research tools included questionnaires and interview forms. The research findings revealed that: The knowledge of developing a social studies teaching system based on the Threefold Training principles includes Sila (morality), Samadhi (concentration), and Panna (wisdom), which aim to enhance the learning and development of students in terms of morality, mental discipline, and wisdom, with the goal of achieving high-quality and sustainable academic success. The assessment of the current problems and needs of the social studies teaching system development based on the Threefold Training principles to enhance the academic achievement of high school students in Nakhon Sawan Province showed that the overall problems and needs were at a high level ( = 3.85). The development of the social studies teaching system based on the Threefold Training principles to achieve the academic achievement of high school students in Nakhon Sawan Province identified five components: Context, input factors, process, outcome, and evaluation and improvement. The evaluation and certification of the social studies teaching system development based on the Threefold Training principles for high school students in Nakhon Sawan Province indicated that the experts' opinions on the system's appropriateness were at the highest level ( = 4.61).